Skill profile of logistics professionals and implications to educational providers - Vidya Ramani (2010)
The logistics industry has evolved from a simple operational and non-profit making concept to a tactical and more recently, strategic concept in most organisations. In the past it mainly focused on procurement, maintenance and transportation of military facilities, materials and personnel. Presently logistics has slowly developed to focus primarily on economics and eventually to a diverse and key component of business strategy, differentiation and connection to customers. Logistics works on knowledge based not only between the supplier and customer, but throughout the whole market. This would integrate the entire organisation in the market to work as a whole and to be able to take advantage on the efficiency, effectiveness, quality and monetary differences that can arise in the world. Logistics skills are portrayed as logical concepts in most organisations; this study will empirically use the HNV framework to test the importance of business and management skills compared to logistics skills in an entry and senior level practitioners. This study also investigates which competences are required in logistics business practice, and whether a difference may be noticed in the actual profiles of logistics professional. The focus of this study is to determine which aspects are needed in modern day logistics as a professional. The study will take the view from logistic professionals working in the maritime sector as well as the logistic service provider. It shows that there is a difference in the competences for both groups and that logistics still has a long way to go before being fully accepted in the boardroom of an organization. „Logistics professionals are generally under „qualified‟ (Dadzie, 1998). This study will look more into the skill profiles of logistics practitioners and their ability to demonstrate these competencies at work. Educating students to become a logistics professional, requires a certain set of competences to be attained. We will investigate on the educational provider‟s perspective on the skills and competencies that are deemed important in the modern logistics sector.